Pathogenicity of snakehead vesiculovirus in rice field eels (Monopterus albus). (September 2017) - Sun, Lindan; Tu, Jiagang; Yi, Lizhu; Chen, Wenjie; Zhao, Lijuan; Huang, Yunmao; Liang, Rishen; Li, Jun; Zhou, Meng; Lin, Li
Abstract: Snakehead vesiculovirus (SHVV) has caused mass mortality to cultured snakehead fish in China, resulting in enormous economic losses in snakehead fish culture. In this report, the whole genome of SHVV was sequenced. Interestingly, it shared more than 94% nucleotide sequence identity with Monopterus albus rhabdovirus (MoARV), which has caused great economic loss to cultured rice field eel ( Monopterus albus ). Therefore, the concern of cross-species infection of these viruses prompted us to investigate the susceptibility of rice field eel to SHVV infection. The results showed that rice field eel was susceptible to SHVV in both intracoelomical injection and immersion routes. Severe hemorrhage was observed on the skin and visceral organs of SHVV-infected rice field eels. Histopathological examination showed vacuoles in the tissues of infected liver, kidney and heart. Viral RNA or protein was detected in the tissues of infected fish by reverse transcription polymerization chain reaction (RT-PCR), in situ hybridization (ISH), or immunohistochemistry assay (IHC). Investigation of the epidemic of vesiculovirus in rice field eel as well as other co-cultured fish is invaluable for the prevention of vesiculovirus infection. Highlights: The whole genome of SHVV was sequenced and it was high identical to that of MoARV. Rice field eel was susceptible to SHVV infection. The tissues of SHVV infected eel were characterized by RT-PCR, ISH and IHA.